ANALISIS SISTEM KOMUNIKASI PENUNJANG EKONOMI KREATIF BERBASIS POTENSI LOKAL (STUDI KASUS KOMUNITAS BANDUNG CREATIVE CITY FORUM (BCCF)) - Dea Christina; Muhammad Zaini Dahlan (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
Development focus has been evolved. Nowadays, we are in the Age of Creative Economy which mobilized mostly by  Creative  Industry.  However,  Indonesia  has  benefited  in  terms  of  developing  this  sector,  since  it  has  2 acknowledged advantages, such as demographic segmentation and ecosystem buffer and support. Unfortunately, it is not enough to make ideal and successful creative ecosystem. Communication in the system should also be developed. BCCF is a supporting communication system in the level of city, who can be an agent of change and a  creative  hub  between  stakeholder  and  community.  Still,  it  has  limitation.  To  give  some  recommendation  to improve  the  communication  process  in  this  supporting  communication  system  is  the  purposes  of  this  paper. Blackbox analysis shows there are some elements in the system such as, controllable input, uncontrollable input, management,  environment,  controllable  output  and  uncontrollable  output.  We  should highlight  uncontrollable input like youth motivation, community readiness and stakeholder commitment which are easily up and down. It will influence how the system achievement, gaining expected output or unexpected output. Based on the analysis, the  communication  strategy  should  refer  to  communication  managerial.  It  means  communication  process  must be appropriated with the most user in the system, which is the youth.  Keywords: communication system, creative economy, local potential